2014
DOI: 10.1016/j.healthplace.2014.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Food environment, walkability, and public open spaces are associated with incident development of cardio-metabolic risk factors in a biomedical cohort

Abstract: We investigated whether residential environment characteristics related to food (unhealthful/healthful food sources ratio), walkability and public open spaces (POS; number, median size, greenness and type) were associated with incidence of four cardio-metabolic risk factors (pre-diabetes/diabetes, hypertension, dyslipidaemia, abdominal obesity) in a biomedical cohort (n=3205). Results revealed that the risk of developing pre-diabetes/diabetes was lower for participants in areas with larger POS and greater walk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
108
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 130 publications
(114 citation statements)
references
References 17 publications
4
108
1
1
Order By: Relevance
“…These finding showed the benefit of having healthier food retailers around schools, and ideally zero convenience stores, which could improve both sides of the energy balance. Lastly, contrary to our hypothesis and prior neighborhood studies, 21,28 no park or open space, of any size, within a 1-mile buffer from school was associated with children's level of fitness. Only a higher number of parks larger than 12.5 acre showed a negative association with females' average-PACER, perhaps due to personal safety concerns.…”
Section: Discussioncontrasting
confidence: 99%
“…These finding showed the benefit of having healthier food retailers around schools, and ideally zero convenience stores, which could improve both sides of the energy balance. Lastly, contrary to our hypothesis and prior neighborhood studies, 21,28 no park or open space, of any size, within a 1-mile buffer from school was associated with children's level of fitness. Only a higher number of parks larger than 12.5 acre showed a negative association with females' average-PACER, perhaps due to personal safety concerns.…”
Section: Discussioncontrasting
confidence: 99%
“…While studies evaluating the built environment have grown rapidly over the past decade [10, 11, 19–24], gaps in data acquisition and consistent methods for measuring built environment characteristics have hampered the adoption of evidence into planning and practice. Participants suggested “ better co-ordination, alignment, and standardization of built environment metrics and performance measures” that could be “ easily adopted by policymakers and planners ”; and greater access to low cost or publicly available data sources (including “ open access data ”) that would increase the capacity for ongoing surveillance work, allowing for comparisons over time and across regions.…”
Section: Resultsmentioning
confidence: 99%
“…47 Paquet et al (2014) found the risk of developing pre-diabetes or diabetes to be lower among Australian adults living in areas with larger public open spaces and higher walkability, although no such relationships were observed for the risk of hypertension or dyslipidemia. 48 Sundquist et al (2015) observed an association between higher walkability and lower incidence of type 2 diabetes over a three-year follow-up period in Swedish adults, but this relationship did not persist after controlling for individual-level sociodemographic characteristics. 49 Examining older adults in the United States over a ten-year period, Christine et al (2015) found a lower incidence of type 2 diabetes among those with greater access to healthy food and physical activity resources.…”
Section: Introductionmentioning
confidence: 98%